The COVID-19 Pandemic and Religious Travel: Present and Future Trends - Olsen, Daniel H. (The international journal of religious tourism and pilgrimage, 2020)
The COVID-19 pandemic of 2020 has had dramatic effects on both the health and economic stability of countries around the world. While several scholars and media commentators have suggested that the pandemic would be a good time to reset an unsustainable tourism system, left out of these discussions has been the impacts on religion and religious travel. The purpose of this paper is to review the impacts of the COVID-19 pandemic on religion and religious travel, including the tensions that have arisen between religious communities, governments and health officials. The paper then discusses potential futures regarding religious travel in a post-COVID-19 and post-secular world.